Supplements for strength-power athletes - Campbell, B. I.; Wilborn, C. D.; La Bounty, P. M. (Strength and Conditioning Journal, 2010)
STRENGTH-POWER ATHLETES IMPROVE EXERCISE PERFORMANCE PRIMARILY BY IMPROVING THEIR SPORT-SPECIFIC SKILLS. IN ADDITION, EXERCISE PERFORMANCE CAN BE ENHANCED BY IMPROVING STRENGTH, LEAN MUSCLE MASS, AND ANAEROBIC EXERCISE PERFORMANCE. SEVERAL SPORTS SUPPLEMENTS HAVE BEEN DOCUMENTED TO ENHANCE THESE ATTRIBUTES, INCLUDING CREATINE MONOHYDRATE, BETA-ALANINE, [beta]-HYDROXY [beta]-METHYLBUTYRATE, AND PROTEIN.